A comparison of sex identification methods based on lip furrow pattern - Topczyłko, Aleksandra; Borysławski, Krzysztof; Nowakowski, Dariusz (Anthropological Review, 2018)
The objective of the study was to specify the method with the highest probability of correct sex identification based on lip furrow pattern. Three methods were verified: Vahanwala’s method, identification based on the mid-section of lower lip print and our own method. The examined group included 242 persons aged 15- 30 years, 68.6% females and 31.4% males. Cheilograms were taken with the method proposed by Vanahwala, modified in such a way that the prints of lower and upper lips were taken separately. The lip furrow patterns were classified according to Suzuki and Tsuchihashi, modified to include horizontal furrows which were considered by Renaud. In all the quadrants patterns II, III and VI prevailed among males and patterns I, I’ and II among females. Females were more frequently diagnosed correctly than males. Our method in which all the lip print was analysed without division into quadrants was the most effective, while Vahanwala’s method was the least so.